2008
DOI: 10.1186/1532-429x-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of myocardial infarction by cardiovascular magnetic resonance predicts future cardiovascular events in patients with ischemic cardiomyopathy

Abstract: Background: Cardiovascular magnetic resonance (CMR) can provide quantitative data of the myocardial tissue utilizing high spatial and temporal resolution along with exquisite tissue contrast. Previous studies have correlated myocardial scar tissue with the occurrence of ventricular arrhythmia. This study was conducted to evaluate whether characterization of myocardial infarction by CMR can predict cardiovascular events in patients with ischemic cardiomyopathy (ICM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…15) The absence of a significant relationship between infarct size and LV remodeling in our MI population without early revascularization is consistent with the findings of previous post-MI studies with heterogeneous populations regarding early revascularization. 3,6,8,9,[17][18][19] Our finding and the results of these studies may imply that in patients without early revascularization LV remodeling is mainly dependent on factors beyond infarct tissue characteristics. Such factors include persistent or recurrent ischaemia, pressure and volume overload hypertrophy, neurohormonal and biophysical factors, and genetic mechanisms such as adapted gene expression in the setting of heart failure.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…15) The absence of a significant relationship between infarct size and LV remodeling in our MI population without early revascularization is consistent with the findings of previous post-MI studies with heterogeneous populations regarding early revascularization. 3,6,8,9,[17][18][19] Our finding and the results of these studies may imply that in patients without early revascularization LV remodeling is mainly dependent on factors beyond infarct tissue characteristics. Such factors include persistent or recurrent ischaemia, pressure and volume overload hypertrophy, neurohormonal and biophysical factors, and genetic mechanisms such as adapted gene expression in the setting of heart failure.…”
Section: Discussionmentioning
confidence: 68%
“…9) However, most previous CE-CMR studies that investigated the relationship between infarct size and cardiac remodeling did not measure the size of the peri-infarct zone. [2][3][4][5][6]8,9,[14][15][16]18,19) The only exception was a study by Heidary,et al,17) who found in a population of patients with ischemic cardiomyopathy, no significant relation between infarct tissue characteristics (including peri-infarct size) and both LV geometry and function.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Due to latter mentioned reasons we did not focus on grey zone analysis, but rather total infarct volume in the presented study. Yokota and colleagues showed in their study that patients with a composite end-point of ventricular arrhythmia, syncope and death during a mean follow-up period of 20 ± 16 months had larger infarcts than patients without an end-point [26]. They did not find differences for left ventricular enddiastolic and end-systolic volumes and for left ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 86%